On Dignity Before Natural Rights - Jeliński, Edward (Sensus Historiae, 2022)
The generality, absoluteness, and universality of natural rights has an impact on the issue of human dignity, understood (in general terms) in two ways: firstly, as a specific attitude determining the way of being (existence) of a particular human - an individual; secondly, as a property belonging to man by nature, stimulated by the world values and its ontic status.